Bacterial pneumonia co-infection in COVID-19 patients - Abdul Karim, Othman; Intan Suhana Munira, Mat Azmi; Mohd Nazri, Ali (2020)
The objective of this study was to highlight the emergence of COVID-19 bacteria pneumonia co-infections in patients infected with SARS-Cov-2 and risk factors related to its incidence and outcomes. We reported two cases of elderly patients with multiple comorbidities infected with SARS-Cov-2 and developed COVID-19 bacterial pneumonia requiring admission to intensive care unit (ICU) with one mortality preceded by septicemic shock and multi-organ failures. Observing the potential risk factors for being infected with SARS-Cov-2 and developing COVID-19 bacterial pneumonia we strongly advocate for rapid detection of COVID-19 bacterial pneumonia in SARS-Cov-2 infected patients and rapidly characterized the bacterial involved for a better outcome and importantly for efficient antimicrobial stewardship. COVID-19 bacterial pneumonia is an emerging disease requiring rapid detection and bacterial characterization with the ongoing management for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2